2022
DOI: 10.1002/smll.202203448
|View full text |Cite
|
Sign up to set email alerts
|

TfR Aptamer Enhanced Blood‐Brain Barrier Penetration of Biomimetic Nanocomplexes for Intracellular Transglutaminase 2 Imaging and Silencing in Glioma

Abstract: Engineering a versatile nanocomplex integrating effective penetration of the blood‐brain barrier (BBB), accurate diagnosis, and boosting therapy has always been an intractable challenge in glioblastoma multiforme (GBM). Herein, biomimetic nanocomplexes (TMPsM) for single intracellular transglutaminase 2 (TG2)‐triggered self‐assembly imaging and RNAi therapy for GBM are subtly developed. To prove the concept, transferrin receptor (TfR) aptamer‐modified brain metastatic tumor cell membrane is prepared as the she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Currently, receptor-mediated targeted nanodrug delivery systems often rely on modifying exogenous ligands, such as transferrin aptamers, apolipoprotein E peptides, and iRGD peptides. , Notably, these targeted nanodrug delivery systems may combine with endogenous proteins to form protein coronas in vivo , resulting in poor targeting . Therefore, we chose serum EXO with TfR as the coating of NPs, which can fully use endogenous Tf to achieve the capacity to target BBB and glioma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, receptor-mediated targeted nanodrug delivery systems often rely on modifying exogenous ligands, such as transferrin aptamers, apolipoprotein E peptides, and iRGD peptides. , Notably, these targeted nanodrug delivery systems may combine with endogenous proteins to form protein coronas in vivo , resulting in poor targeting . Therefore, we chose serum EXO with TfR as the coating of NPs, which can fully use endogenous Tf to achieve the capacity to target BBB and glioma cells.…”
Section: Resultsmentioning
confidence: 99%
“…KCC009 disrupted fibronectin assembly in the ECM, interfering with its pro-survival characteristics [161]. Recently, in contrast with the findings of Dyer and colleagues, it has been reported that biomimetic nanocomplexes containing TG2 small interfering RNA (siRNA) can sensitize U87MG cells to TMZ increasing apoptosis [162].…”
Section: Tg2 In Adult-type Diffuse Gliomasmentioning
confidence: 96%
“…116,117 Su et al constructed a core-shell biomimetic nanoprobe (TMPsM) for RNAi therapy of GBM, which was composed of hollow MnO 2 carrying Pep-TPE and siRNA as the core, and TfR-aptamer-modified B16F10 cell membrane as the shell. 118 They proved that TMPsM exhibited the ability of TG2 gene silencing to induce apoptosis in vitro, 119 TG2 stimulated self-assembled AIE imaging to accurately diagnose GBM in vivo, and the released siRNA effectively silenced TG2 expression to induce apoptosis, inhibiting the development of orthotopic U87MG-luciferase tumor. For the first time, TMPsM achieved accurate diagnosis and effective treatment of GBM through TG2-triggered self-assembly imaging and RNAi therapy.…”
Section: 26mentioning
confidence: 99%